Comparison of Murabahah Akad with Ijarah Muntahiya Bit Tamlik Akad in KPR Faedah Financing In Bank Bri Syariah KCP Kopo (Kabupeten Bandung) - Sonia, Gina; Sudirja, Andri Marta (Edukasi: Journal of Educational Research, 2021)
Bank syariah are banks that operate by Sharia principles by following its teachings and staying away from the prohibitions listed in the Al-Quran and Hadith, including practices that were carried out during the time of the Prophet Muhammad, namely accepting deposits, channeling funds, and making transfers have become a part that is not separated from the life of the Islamic ummah even since the time of the Prophet. KPR Faedah is a type of service provided by banks to customers running in the housing sector, banks are expected to provide financing to customers to purchase houses or renovate houses, apartments, shop houses, shop houses, kiosks, or transferring KPR Faedah take-over from other banks. . KPR Faedah BRI Syariah KCP Kopo uses the Murabahah (sale and purchase) contract or the Ijārah Muntahiya Bit Tamlik contract (lease-purchase). However, Bit Tamlik's Ijarah Muntahiya contract was not very enthusiastic. This study aims to compare the Murabahah contract and the Ijarah Muntahiya Bit Tamlik contract on KPR Faedah BRI Syariah KCP Kopo financing so that we can know the similarities and differences as well as the advantages and disadvantages of the two contracts. The type of data used in this study is qualitative data, qualitative data is data obtained directly from the field in the form of characteristics, characteristics, explanations, and information in the form of knowledge, thoughts, and theories. The research method used is the comparative method, namely stating the comparison between one sample or variable with another sample or variable. Sources of data used are primary data and secondary data. Data collection techniques used were observation, interviews, literature study, and documentation. The results showed a comparison of the Murabahah contract and the Ijarah Muntahiya Bit Tamlik contract on KPR Faedah BRI Syariah KCP Kopo financing seen from several aspects, namely the similarities and differences, advantages and disadvantages, so it can be concluded that the Murabahah contract cannot adjust the price when the market price rises because of the selling price. and the margin is set at the beginning, in contrast to Ijarah Muntahiya Bit Tamlik, with the review of umrah, the rental price can follow the market price at that time. However, at Bank BRI Syariah KCP Kopo KPR Faedah customers prefer the Murabaha contract, as well as the researchers, chose to use the Murabaha contract in this KPR Faedah product because the process is easier and the installments remain until the end of the period.